Infected hardware after surgical stabilization of rib fractures: Outcomes and management experience. Issue 5 (May 2016) - Thiels, Cornelius A.; Aho, Johnathon M.; Naik, Nimesh D.; Zielinski, Martin D.; Schiller, Henry J.; Morris, David S.; Kim, Brian D.
Abstract : BACKGROUND: Surgical stabilization of rib fracture (SSRF) is increasingly used for treatment of rib fractures. There are few data on the incidence, risk factors, outcomes, and optimal management strategy for hardware infection in these patients. We aimed to develop and propose a management algorithm to help others treat this potentially morbid complication. METHODS: We retrospectively searched a prospectively collected rib fracture database for the records of all patients who underwent SSRF from August 2009 through March 2014 at our institution. We then analyzed for the subsequent development of hardware infection among these patients. Standard descriptive analyses were performed. RESULTS: Among 122 patients who underwent SSRF, most (73%) were men; the mean (SD) age was 59.5 (16.4) years, and median (interquartile range [IQR]) Injury Severity Score was 17 (13–22). The median number of rib fractures was 7 (5–9) and 48% of the patients had flail chest. Mortality at 30 days was 0.8%. Five patients (4.1%) had a hardware infection on mean (SD) postoperative day 12.0 (6.6). Median Injury Severity Score (17 [range, 13–42]) and hospital length of stay (9 days [6–37 days]) in these patients were similar to the values for those without infection (17 days [range, 13–22 days] and 9 days [6–12 days], respectively). Patients with infection underwent a median (IQR) of 2 (range, 2–3) additional operations, which included wound debridement (n = 5), negative-pressure wound therapy (n = 3), and antibiotic beads (n = 4). Hardware was removed in 3 patients at 140, 190, and 192 days after index operation. Cultures grew only gram-positive organisms. No patients required reintervention after hardware removal, and all achieved bony union and were taking no narcotics or antibiotics at the latest follow-up. CONCLUSIONS: Although uncommon, hardware infection after SSRF carries considerable morbidity. With the use of an aggressive multimodal management strategy, however, bony union and favorable long-term outcomes can be achieved. LEVEL OF EVIDENCE: Therapeutic study, level V.